Thailand and the World Tomato: Globalization, New Agricultural Countries (NACs) and the Agrarian Question - Rosset, Peter; Rice, Robert; Watts, Michael (The International Journal of Sociology of Agriculture and Food, 2021)
In this article we explore the genesis and character of the so called “new agricultural countries” (NACs), focusing on Thailand and its tomato industry in particular. We begin with a brief overview of the rise and character of the NACs, turning then to the Thai case and its peculiarities and form. We examine various dimensions of the rise of high value foods (HVF), globalization, turmoil and growth in the agro-food economy. We ask the general question of how and in what senses the NACs are genuinely global in their agro-food sectors, in terms of production and institutional relationships. These questions are explored in detail using a survey of contract farmers in the Isaan region of northeast Thailand. These are small, peasant farmers who produce hybrid tomato seeds and/or processing tomatoes, for both the transnational seed industry and domestic buyers. We end by situating our findings about the agro-food industry and contract farming within a discussion of Kautsky’s “agrarian question” of a century ago.